2017
DOI: 10.21887/ijvsbt.v12i3.7109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Supplementation of Crushed Flaxseed and Soybean Oil on Ovarian Functions in Postpartum Jersey Crossbred Cows

Abstract: The effect of dietary supplementation of crushed flaxseed and soybean oil on ovarian function in postpartum Jersey crossbred cows was studied. Total 30 postpartum normally calved cows from 2nd to 4th lactation were randomly divided into three equal groups. Cows from group T1 and T2 were fed with dietary supplementation of crushed flaxseed @ 15% of DM requirement from day 25 to day 70 postpartum and with soybean oil @ 3% of DM requirement of animal from day 50 to day 70 postpartum in addition to routine feed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
8
3
0
Order By: Relevance
“…Supplementation of soybean was effective in increasing the number of medium sized follicles compared to a saturated fat or a highly unsaturated fat (fish oil) supplement and this was associated with higher serum insulin and increased granulose cell proliferation (Poretsky and Kalin, 1987) [13] . In the present study, the significant increase in class II and total number of follicle on day 0 in supplemented group is in accordance with Deshmukh et al (2017) [2] who reported significant increase in class II and total number of follicles after supplementation of soybean oil and flaxseed in post partum cows. The mean total number of class I follicles showed non significant difference between the supplemented and non supplemented groups.…”
Section: Ovarian Response In Different Groups 32 Ovarian Response Osupporting
confidence: 92%
See 4 more Smart Citations
“…Supplementation of soybean was effective in increasing the number of medium sized follicles compared to a saturated fat or a highly unsaturated fat (fish oil) supplement and this was associated with higher serum insulin and increased granulose cell proliferation (Poretsky and Kalin, 1987) [13] . In the present study, the significant increase in class II and total number of follicle on day 0 in supplemented group is in accordance with Deshmukh et al (2017) [2] who reported significant increase in class II and total number of follicles after supplementation of soybean oil and flaxseed in post partum cows. The mean total number of class I follicles showed non significant difference between the supplemented and non supplemented groups.…”
Section: Ovarian Response In Different Groups 32 Ovarian Response Osupporting
confidence: 92%
“…The mean bearing different superscripts in a row, differs significantly. The present finding regarding mean growth rate (mm/day) of ovulatory follicle, mean day of emergence of new follicle was in accordance with Deshmukh et al (2017) [2] who reported a significant difference in growth rate and the mean day of emergence of new follicle with supplementation of soybean oil and crushed flaxseed as compared to no fat supplementation group. Similarly, the mean day of emergence of new follicle after injection of first GnRH was in close agreement with Twagiramunga et al (1995) [19] .…”
Section: Follicular Dynamic During Estrus Synchronization In Differensupporting
confidence: 92%
See 3 more Smart Citations